Towards improving the assessment of rainforest carbon: Complementary evidence from repeated diameter measurements and dated wood - Angoboy Ilondea, B.; Mil, T. de; Hubau, W.; Acker, J. van; Bulcke, J. van den; Fayolle, A.; Bourland, N.; Kapalay, O.; Chantrain, A.; Ewango, C.; Beeckman, H. (Elsevier, 2020)
We explore whether a growth-ring analysis can produce additional information about carbon budgets in tropical forests. Such forests are characterized by a high number of species and by trees that rarely have anatomically distinct annual growth rings, which hampers the application of dendrochronological tools in carbon balance assessments in the tropics. We use forest inventory data and archived annual diameter measurements from the Luki Biosphere Reserve in the southwestern margin of the Congo Basin forest massif. In addition, dated wood data are available from the same location thanks to tag nail traces that allow for the measurement of growth increments over a period of 66 years. We find that precise increment measurements based on dated wood are advisable for small subsets of many less abundant species and for functional species groups characterized by slow growth. The dated wood approach shows that many understory trees with non-periodical rings remain in a steady state for long periods of time. These results suggest a dated wood approach is advisable for studies of growth trajectories of individual trees that might be of importance for carbon assessments in degraded forests.